On the CCD Calibration of Zwicky galaxy magnitudes and The Properties of Nearby Field Galaxies - Gaztanaga, E; Dalton, G (1999)
We present CCD photometry for galaxies around 204 bright (m_Z < 15.5) Zwicky galaxies in the equatorial extension of the APM Galaxy Survey, sampling and area over 400 square degrees, which extends 6 hours in right ascension. We fit a best linear relation between the Zwicky magnitude system, m_Z, and the CCD photometry, B, by doing a likehood analysis that corrects for Malmquist bias. This fit yields a mean scale error in Zwicky of 0.38 mag per magnitude: ie Delta m_Z = (0.62 ± 0.05) Delta B and a mean zero point of <b-m_z> = -0.35 ± 0.15 mag. The scatter around this fit is about 0.4 mag. Correcting the Zwicky magnitude system with the best fit model results in a 60% lower normalization and 0.35 mag brighter M_* in the luminosity function. This brings the CfA2 luminosity function closer to the other low redshift estimations (eg Stromlo-APM or LCRS). We find a significant positive angular correlation of magnitudes and position in the sky at scales smaller than about 5 armin, which corresponds to a mean separation of 120 Kpc/h. We also present colours, sizes and ellipticities for galaxies in our fields which provides a good local reference for the studies of galaxy evolution.</b-m_z>